Tatalaksana Cuci Tangan Dan Penanganan Luka Sederhana Pada Petani Sawit Di Desa Sari Galuh, Kampar: Pendekatan Kesehatan Masyarakat - Ulfah, Ulfah; Asni, Enikarmila; Hamidy, Yulis; Juananda, Desby; Maryanti, Yossi; Sonia Sahara, Nabilla; Dhani, Rahma; Andri, Sofyan; Aiyulie Novri, Dhini; Agung Soripada, Timotius (LPPM UMRI, 2026)
This community service programme aimed to improve hygiene awareness and basic wound-care skills among palm-oil farmers in Sari Galuh Village, Kampar District, Riau Province. Farmers frequently experience minor injuries from sharp tools, palm thorns, and exposure to dirt, which increases infection risk. However, proper hand-washing practice and simple wound-care knowledge are still lacking. The intervention included hand-washing training based on WHO standards, education on simple wound care, provision of hand-washing facilities, and distribution of first-aid kits. A total of 41 participants attended the programme. Evaluation using pre-test and post-test instruments showed significant improvement in participants’ knowledge and skills. The program effectively strengthened preventive health behaviours and is recommended as a sustainable community health empowerment model for agricultural groups.